Crime and crime trends in different urban environments - Wikström, Per-Olof H. (Journal of quantitative criminology, 1990)
This is a study of crime and crime trends in different urban environments in Stockholm. The study is in two major parts. First, on the basis of a study of the factorial social ecology of Stockholm in 1980, the city is grouped into major urban environments, and thereafter the criminality in these different urban environments is studied cross sectionally for 1982. Second, the trends in crime in the city of Stockholm and its different types of urban environments are studied over a 20-year period (1968–1987). The findings show significant differences between types of urban environments in rates of crimes, offenders and victims, crime structure, and crime and distance. Also, the trends in crime were significantly different between different types of urban environments.